2016
DOI: 10.1080/10538712.2016.1236871
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies and Depression Among College Students Following Child Sexual Abuse in Turkey

Abstract: The objective of this study was to investigate the relationship between type of coping style and depression in college students with child sexual abuse experience. A total of 1,055 college students completed self-report measures to assess depressive symptoms, coping strategies, and child sexual abuse history. This study was conducted with a subset of 125 college students who reported that they had been sexually abused in childhood. They were divided into depressive and nondepressive groups according to their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Yılmaz Irmak et al (2016) created the TLEF to evaluate traumatic life events such as migration and the death of a family member. Participants are asked whether they have experienced any of 14 traumatic life events in the form.…”
Section: Methodsmentioning
confidence: 99%
“…Yılmaz Irmak et al (2016) created the TLEF to evaluate traumatic life events such as migration and the death of a family member. Participants are asked whether they have experienced any of 14 traumatic life events in the form.…”
Section: Methodsmentioning
confidence: 99%
“…Neuropsychiatric Disease and Treatment 2023:19 2272 compensate for the emptiness and insecurity in their hearts. 11,24,27,28 Therefore, the study formulated hypothesis 2: Coping style will serve as a mediator between childhood trauma and NSSI (childhood trauma → coping style → NSSI).…”
Section: Dovepressmentioning
confidence: 99%
“…On the other hand, childhood trauma is an unhealthy environmental factor imposed on individuals by parents or caregivers, and children in this environment may form problems such as poor interpersonal trust and learned helplessness; thus, they likely adopt NC styles, such as smoking, alcohol abuse, drug dependence or NSSI to release and compensate for the emptiness and insecurity in their hearts. 11 , 24 , 27 , 28 Therefore, the study formulated hypothesis 2: Coping style will serve as a mediator between childhood trauma and NSSI (childhood trauma → coping style → NSSI).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that boys had a higher score of "pointing to emotional response" than girls. It may be that girls' psychological development is earlier than boys', making them more rational and mature than boys in dealing with examinations and other problems (Yılmaz, Aksel, & Thompson, 2016). In the ethnic areas of Qinghai Province, the "patriarchal" ideology is still more serious.…”
Section: Differences In the Basic State Of Coping Style Among Middle mentioning
confidence: 99%